Carfilzomib–dexamethasone vs bortezomib–dexamethasone in relapsed or refractory multiple myeloma by cytogenetic risk in the phase 3 study ENDEAVOR - Chng, W.-J.; Goldschmidt, H.; Dimopoulos, M.A.; Moreau, P.; Joshua, D.; Palumbo, A.; Facon, T.; Ludwig, H.; Pour, L.; Niesvizky, R.; Oriol, A.; Rosiñol, L.; et al. (Leukemia, 2017)
The randomized phase 3 study ENDEAVOR demonstrated a statistically significant and clinically meaningful improvement in progression-free survival (PFS) for carfilzomib and dexamethasone (Kd) vs bortezomib and dexamethasone (Vd) in relapsed or refractory multiple myeloma (MM). We conducted a preplanned subgroup analysis of ENDEAVOR to evaluate Kd vs Vd by cytogenetic risk. Of 785 patients with known cytogenetics, 210 (27%) had high-risk cytogenetics (Kd, n=97 (25%); Vd, n=113 (28%)) and 575 (73%) had standard-risk cytogenetics (Kd, n=284 (75%); Vd, n=291 (72%)). Median PFS in the high-risk group was 8.8 months for Kd vs 6.0 months for Vd (hazard ratio (HR), 0.65; 95% confidence interval (CI), 0.45–0.92; P=0.0075). Median PFS in the standard-risk group was not estimable for Kd vs 10.2 months for Vd (HR, 0.44; 95% CI, 0.33–0.58; P<0.0001). Overall response rates were 72.2% (Kd) vs 58.4% (Vd) in the high-risk group and 79.2% (Kd) vs 66.0% (Vd) in the standard-risk group. In the high-risk group, 15.5% (Kd) vs 4.4% (Vd) achieved a complete response (CR) or better. In the standard-risk group, 13.0% (Kd) vs 7.9% (Vd) achieved ⩾CR. This preplanned subgroup analysis found that Kd was superior to Vd in relapsed or refractory MM, regardless of cytogenetic risk.Leukemia advance online publication, 3 February 2017; doi:10.1038/leu.2016.390. © 2017 The Author(s)